2012
DOI: 10.7727/wimj.2011.103
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Cataract with Serum Lipids, Glucose and Antioxidant Activities: A Case-control Study

Abstract: The aim of this study is to evaluate the relationship between cataract development and serum lipids, glucose as well as antioxidants in a case-control study. Methods: Ninety patients with cataract and 90 age-and sex-matched healthy controls were investigated. Lipid profiles including triglyceride (Tg), total serum cholesterol (Chol) and cholesterol content in high-density lipoproteins (HDL chol) and low-density lipoproteins (LDL chol) as well as fasting glucose (FBS) were measured for all subjects. Plasma oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 21 publications
7
20
0
Order By: Relevance
“…Additionally, high LDL was an independent risk factor for nuclear cataract (OR: 1.19, P = 0.047), but LDL and HDL were not associated with cortical cataract. Previous studies have also reported the associations between high LDL and low HDL levels and cataract . In the Beaver Dam Eye Study and the Framingham Offspring Heart Study, low HDL was associated with cortical cataract and PSC, respectively.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Additionally, high LDL was an independent risk factor for nuclear cataract (OR: 1.19, P = 0.047), but LDL and HDL were not associated with cortical cataract. Previous studies have also reported the associations between high LDL and low HDL levels and cataract . In the Beaver Dam Eye Study and the Framingham Offspring Heart Study, low HDL was associated with cortical cataract and PSC, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…[35][36][37][38][39] In the Beaver Dam Eye Study 36 and the Framingham Offspring Heart Study, 37 low HDL was associated with cortical cataract and PSC, respectively. Other studies have also found that high LDL 39 and high LDL:HDL ratios 38 were significantly associated with cataract. Oxidative damage and inflammation resulting from abnormal serum cholesterol levels might be the underlying cause of the cataract.…”
Section: Discussionmentioning
confidence: 99%
“…Patents with cataract display excess lipid peroxidation (TBARS) with decreased thiol levels and ferric reducing/antioxidant power; moreover, an increase in dehydroascorbate/ascorbate ratio was observed [284, 285]. A study of polymorphisms of SOD-1, CAT, and GPx genes in cataract patients found that G/G genotype of the SOD-1 (251A/G polymorphism) was associated with an increased risk of cataract [286].…”
Section: Miscellaneous Pathologiesmentioning
confidence: 99%
“…It is developed in the crystalline lens of the eye in various degrees; from complete opacity to obstructing the passage of light. Lens opacity was detected in hypercholesterolemic patients with or without ischemic heart disease [73,74] and those with elevated levels of cholesterol and triglycerides [75]. Human lens membranes were found to possess the highest cholesterol content with biological importance.…”
Section: Cataractous Lensmentioning
confidence: 98%
“…Hypercholesterolemic patients were found to develop cataractous lens [150] associated with increased oxidative stress and depletion of antioxidants [151].…”
Section: Bioavailability and Pharmacokinetics Of Nutrientsmentioning
confidence: 99%